LEGAL DOCUMENT PLANNING AT RM.ACHUN 178 - Desy Desy; Evi Silvana Muchsinati (ConCEPt - Conference on Community Engagement Project, 2023)
Achun 178 restaurant is a business engaged in Chinese cuisine. This restaurant is located on Trikarsa Ekualita street, Batam. In running his business, the owner stated that there was a problem where this business did not yet have regulations and work contracts where previously there had been cases of employees resigning from the restaurant and opening a new restaurant with the same food recipes. To solve the problems faced by restaurants, the author proposes to assist these businesses in making legal documents consisting of business regulations and work contracts. Business regulations and work contracts that have been made contain the rights and obligations of employers and employees. This is made to align goals and provide harmony to work life at Achun 178 restaurant. Making this legal document is expected to help restaurants minimize problems that exist in the future.